PENGARUH PENGGUNAAN MEDIA AUGMENTED REALITY BERBASIS ASSEMBLR EDU TERHADAP PEMAHAMAN KONSEP SISWA SD KELAS V PADA PEMBELAJARAN IPAS - Luhukay, Rudolf Abraham (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
ABSTRACT Difficulties among elementary school students in understanding abstract concepts in IPAS learning are still frequently encountered, particularly when instructional practices are predominantly conducted using conventional teaching methods. The integration of Augmented Reality (AR) in learning environments can provide students with more tangible learning experiences through clear visualizations and interactive activities. This study aimed to examine the effect of AR-based learning media developed using the Assemblr EDU platform on improving fifth-grade students’ conceptual understanding in IPAS learning. The research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The participants consisted of 55 students divided into two groups: an experimental group of 28 students and a control group of 27 students. The research procedure included a pretest, the implementation of learning activities across four instructional sessions according to the treatment given to each group, and a posttest to measure learning outcomes. Data analysis involved prerequisite statistical tests, N-Gain calculations, and an independent samples t-test with a significance level of 0.05. The results indicated that the average posttest score of the experimental group reached 83.21, which was higher than that of the control group at 73.02. Furthermore, the N-Gain analysis showed that the improvement in conceptual understanding in the experimental group fell into the moderate category (0.58), while the control group showed an increase ranging from low to moderate (0.34). The hypothesis testing also revealed a statistically significant difference (p = 0.003). Overall, the findings suggest that integrating AR-based learning media through the Assemblr EDU platform can effectively enhance students’ conceptual understanding in IPAS learning at the elementary school level. ABSTRAK Kesulitan siswa sekolah dasar dalam memahami konsep-konsep abstrak pada pembelajaran IPAS masih sering dijumpai, khususnya ketika kegiatan pembelajaran lebih banyak menggunakan metode konvensional. Pengintegrasian Augmented Reality (AR) dalam pembelajaran dapat membantu siswa memperoleh pengalaman belajar yang lebih konkret melalui visualisasi yang jelas dan aktivitas interaktif. Penelitian ini dilakukan untuk mengkaji pengaruh penggunaan media AR berbasis Assemblr EDU terhadap peningkatan pemahaman konsep siswa kelas V dalam pembelajaran IPAS. Metode penelitian yang digunakan adalah quasi-eksperimen dalam kerangka pendekatan kuantitatif dengan desain Nonequivalent Control Group Design. Subjek penelitian terdiri dari 55 siswa yang dibagi ke dalam dua kelompok penelitian, yaitu kelompok eksperimen berjumlah 28 siswa dan kelompok kontrol berjumlah 27 siswa. Prosedur penelitian meliputi pemberian pretest, pelaksanaan pembelajaran selama empat pertemuan sesuai perlakuan pada masing-masing kelompok, serta posttest untuk mengukur hasil belajar. Analisis data dilakukan melalui uji prasyarat statistik, perhitungan N-Gain, dan uji independent sample t-test dengan taraf signifikansi 0,05. Hasil analisis data memperlihatkan bahwa rata-rata skor posttest siswa pada kelas eksperimen mencapai 83,21, sedangkan pada kelas kontrol hanya sebesar 73,02. Berdasarkan analisis N-Gain, peningkatan pemahaman konsep siswa pada kelompok eksperimen termasuk dalam kategori sedang (0,58), sementara pada kelompok kontrol berada pada kategori rendah sampai sedang (0,34). Uji hipotesis menunjukkan adanya perbedaan yang signifikan (p = 0,003). Hasil studi ini memperlihatkan bahwa integrasi media AR melalui platform Assemblr EDU mampu mendukung peningkatan pemahaman konsep siswa pada pembelajaran IPAS di jenjang sekolah dasar.